Novel polyomavirus in the endangered garden dormouse Eliomys quercinus - Emilija Vasiliūnaitė; Monika Repšytė; Eva Marie Kramer; Johannes Lang; Christine Jelinek; Rainer G. Ulrich; Christopher B. Buck; Alma Gedvilaitė (Virology Journal)
Abstract Background The garden dormouse (Eliomys quercinus) has experienced a significant population decline across Europe in recent decades. While habitat loss and climate change are often cited as primary factors, pathogen exposure, either to novel or to previously known, may play a role in such a decline. This study aimed to investigate the presence of polyomaviruses in garden dormice, given that these viruses are highly prevalent and can cause disease, particularly in immunocompromised individuals. Methods The carcasses of garden dormice (n = 89) were collected throughout Germany. Kidney samples were tested for the presence of polyomavirus DNA using nested degenerate and specific diagnostic PCRs. Seroprevalence was assessed from chest cavity fluid samples through an enzyme-linked immunosorbent assay using polyomavirus VP1 virus-like particles produced in yeast. Results A new polyomavirus, related to chimpanzee (Pan troglodytes) polyomaviruses 4 and 5 and human Merkel cell polyomavirus, was identified in the garden dormouse. Two 5,380 bp-length complete viral genomes were sequenced from dormice kidney samples (sequences PQ246041 and PQ246042). Genes encoding the putative structural proteins VP1, VP2, and VP3, as well as the Large, Middle, and small T antigens, containing conserved functional domains were identified. Polyomavirus DNA was detected in 2 of 74 dormice (2.7%, 95% confidence interval: 0-6.4%) through PCR, while 12 of 69 animals (17.4%, 95% confidence interval: 8.4-26.3%) tested positive for polyomavirus-specific antibodies. Conclusions In conclusion, here we describe a novel polyomavirus in the garden dormouse with molecular and serological detection. Pairwise sequence comparison and phylogenetic analysis suggest that this novel virus may represent a novel species within the genus Alphapolyomavirus. Future work should examine if this virus is garden dormouse-specific and whether it is associated with disease in dormice.